Pengembangan Media Pembelajaran Berbasis Aplikasi Quizizz Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematik Siswa pada Masa Pandemi Covid-19 - Rani Rahim; M. Arif Rahman (Universitas Batanghari Jambi, 2022)
The purpose of this research is to find out how the development of learning media based on the Quizizz application is feasible and effective and whether the Quizizz application can improve students’ mathematical problem solving abilities. The media developed is the Quizizz application and a mathematical problem solving ability test. The research subjects were students of class X. The type of research using 4-D model. In testing the feasibility of the media obtained from 5 expert validation. Meanwhile, to see the effectiveness of media, it was obtained from trials of learning media and the results of students’ mathematical problem solving abilities test. Limited trials were conducted on 9 students. The field trial consisted of the first and second field trials carried out on class X. Based on conclusions of the five experts stated that the learning media is included in the category feasible to use. Meanwhile, based on results of the student assessment of the learning media in the very good category. Based on the completeness value, student learning outcomes have met the effectiveness criteria and there is an increase in students’ mathematical problem solving abilities using the Quizizz application.